Transferrin-antibody fusion proteins are effective in brain targeting. - Shin, S U (1995)
In the present study, the receptor binding potential of transferrin (Tf) was linked to an antibody binding specificity. Human Tf was fused to mouse-human chimeric IgG3 at three positions: at the end of heavy chain constant region 1 (CH1), after the hinge, and after CH3. The resulting Tf-antibody fusion proteins were able to bind antigen and the Tf receptor. The CH3-Tf fusion protein showed no complement-mediated cytolysis but possessed IgG receptor I (Fc gamma RI) binding activity. Most importantly, all of the fusion proteins demonstrated significant uptake into brain parenchyma, with 0.3% of the injected dose of the hinge-Tf fusion protein rapidly targeted to the brain. Recovery of iodinated CH3-Tf fusion protein from the brain parenchyma demonstrated that the fusion proteins can cross the blood-brain barrier intact. The binding specificity of these fusion proteins can be used for brain delivery of noncovalently bound ligands, such as drugs and peptides, or for targeting antigens present within the brain.